Maternal Lactobacillus rhamnosus administration impacts neonatal CD4 T-cell activation and prevents murine T helper 2-type allergic airways disease - Smout, Justine; Valentin, Clara; Delbauve, Sandrine; Pauwels, Jeanne; Köhler, Arnaud; Flamand, Véronique (Frontiers in Immunology, 2023)
Gut microbiota plays a role in the neonatal immune education and could influence susceptibility to Th2-type immune disorders, such as allergies, the most prevalent chronic diseases in early childhood. We studied the impact of oral Lactobacillus rhamnosus (L.rhamnosus) supplementation to pregnant/breastfeeding C57BL/6 mice on the development of allergic airways disease in their offspring. We observed that mice, from L.rhamnosus-treated mothers, inoculated with ovalbumin (OVA)-Aluminium hydroxide (ALUM) at 3 days of life and challenged intranasally 4 weeks later showed decreased Th2-associated cytokines, IgE and IgG1, lung eosinophilia and airway hyper-reactivity compared to OVA-sensitized mice from untreated mothers. In that setting, the L.rhamnosus treatment increased the number and maturation of splenic neonatal type 1 conventional dendritic cells (cDC1) that remained largely dominant over the cDC2 and favored their OVA-specific Th1 differentiation. In response to inhaled house dust mite (HDM) allergen, the maternal L.rhamnosus supplementation increased the number of neonatal pulmonary cDC1 expressing lower amount of costimulatory molecules compared with no supplementation and decreased the number of cDC2 without affecting their costimulatory molecules expression. An HDM-specific Foxp3+RORγt+ Treg polarization was monitored in the lung draining lymph nodes. Finally, we confirmed the inhibitory effect of maternal L.rhamnosus treatment on all the measured features of the HDM allergic airways reaction in their offspring. We conclude that maternal L.rhamnosus administration prevents Th2-type allergic airways disease in their neonates by favoring splenic cDC1/Th1 responses against ALUM-adjuvanted OVA or by promoting a pulmonary Foxp3+RORγt+ Treg activation against inhaled HDM.